Detection of selected resistance genes, integrons, Salmonella Genomic Island and plasmids in multidrug resistant Salmonella / Lee Kong Hoe Lee, Kong Hoe. - Lee, Kong Hoe (2012)
The study was to detect and characterize the selected antimicrobial resistance genes, class 1 integron, Salmonella Genomic Island 1 (SGI1) and plasmid profile of 41 selected multidrug resistant (MDR) Salmonella strains of human origin. Salmonella strains harbored blaCTX-M (33.3%) followed by blaTEM (25.0%), blaPSE-1 (13.9%), blaCMY-2 (8.3%) and blaSHV (2.8%) genes. Quinolone or fluoroquinolone-resistant strains harbored qnrB (75.0%) and qnrS (29.2%) genes. Concurrent presence of β-lactamase genes and qnr genes were detected in 9 strains, including S. Lagos (n=1), S. Enteritidis (n=2), S. Farsta (n=2) and S. Typhimurium (n=4). Class 1 integron was detected in 9 strains (S. Albany (n=2), S. Corvallis (n=1), S. Typhimurium (n=1), S. Paratyphi B var Java (n=3), S. Limete (n=1), S. Bovismorbificans (n=1)) and five different gene cassettes, namely aadA2, dfrA1-catB3, blaPSE-1, dfrA1-orfC, and dfrA12-aadA2 were found. Besides, SGI1 was also detected in six class 1 integron-positive strains, including S. Albany (n=2), S. Paratyphi B var Java (n=3), and S. Limete (n=1). To our knowledge, this is the first study reporting on the detection of class 1 integron and SGI1 in S. Limete. Furthermore, 23 plasmid profiles were identified in 30 MDR Salmonella strains and the plasmids ranged from 1.8kb to 65.0kb. Six and nine plasmid-positive strains harbored only β-lactamase gene(s) or qnr gene(s), respectively; while, nine plasmid-positive strains harbored both β-lactamase gene and qnr gene. In conclusion, concurrent resistant to extended spectrum cephalosporins (ESCs) and fluoroquinolones were observed and this phenomenon needs to be concerned because it will limit the therapeutic options for severe Salmonella infections.